Rock friction and earthquake prediction - Byerlee, James; Wyss, Max (Contributions to current research in geophysics (CCRG) ; 6, 1978)
Proceedings of a conference on 'Experimental studies of rock friction with application to earthquake prediction' held at Stanford University on April 28-30, 1977.